Generalization of Tools for Internalization of Negative Externalities in the European Union: Conclusions for Ukraine - Serdiuk, O.; Petrova, I. (Економічний вісник Донбасу, 2020)
A comparative analysis of the tools of internalization of negative external. Based on the generalization and assessment of the possibilities of using the tools of internalization of negative externalities, the areas of application, as well as the strengths and weaknesses of direct regulation, economic (market) and institutional tools are identified. The tools of direct regulation are characterized, and it is found that they do not minimize economic costs and have high administrative costs. The economic (market) instruments of regulation are analyzed and it is revealed that in European practice such instruments as trade in permits (market instrument) and emission charges (Pig tax) are widely used. Institutional regulatory tools such as disclosure strategies and voluntary initiatives are considered and analyzed. It is substantiated that there is no universal tool that would provide full internalization of negative externalities. It is revealed that in modern conditions, the most successful solution will be the development and improvement of tools of direct state regulation of negative externalities in combination with economic (market) instruments, because both economic and market instruments can work effectively and purposefully only if environmental standards are established and observed. environmental quality. The characteristic of application of tools of internalization of negative external effects on an example of slag dumps is given.